Drug Release from Thermo‐Responsive Polymer Brush Coatings to Control Bacterial Colonization and Biofilm Growth on Titanium Implants. Issue 11 (5th May 2021) - Choi, Hongsuh; Schulte, Anna; Müller, Mareike; Park, Mineon; Jo, Suenghwan; Schönherr, Holger
Abstract: Despite decades of biomedical advances, the colonization of implant devices with bacterial biofilms is still a leading cause of implant failure. Clearly, new strategies and materials that suppress both initial and later stage bacterial colonization are required in this context. Ideal would be the implementation of a bactericidal functionality in the implants that is temporally and spatially triggered in an autonomous fashion at the infection site. Herein, the fabrication and validation of functional titanium‐based implants with triggered antibiotic release function afforded via an intelligent polymer coating is reported. In particular, thermo‐responsive poly(di(ethylene glycol) methyl ether methacrylate) (PDEGMA) brushes on titanium implants synthesized via a surface‐initiated atom transfer radical polymerization with activators regenerated through the electron transfer technique (ARGET ATRP) allows for a controlled and thermally triggered release of the antibiotic levofloxacin at the wound site. Antibiotic loaded brushes are investigated as a function of thickness, loading capacity for antibiotics, and temperature. At temperatures of the infection site >37 °C the lower critical solution temperature behavior of the brushes afforded the triggered release. Hence, in addition to the known antifouling effects, the PDEGMA coating ensured enhanced bactericidal effects, as demonstrated in initial in vivo tests with rodents infected with Staphylococcus aureus . Abstract : A new strategy to suppress the initial bacterial colonization on titanium implants is reported that is based on a thermally triggered antibiotic release function afforded via intelligent polymer coatings. Poly(di(ethylene glycol) methyl ether methacrylate) brushes afforded an antifouling function and ensured antibacterial effects by triggered levofloxacin release, as demonstrated in initial in vivo tests with rodents infected with Staphylococcus aureus .